Carrimebac, the town that walked eaudiobook - Moore, David Barclay (OrangeSky Audio, 2022)
A stunning feat of original storytelling from the recipient of the 2018 John Steptoe New Talent Author Award In a boldly transportive original tale, David Barclay Moore infuses history with wry folk wisdom, metaphorical power, and a splash of magic. The Civil War may be over, but times are not substantially improved for the freed Black citizens of Walkerton, Georgia, who are shunned by the white folks of the surrounding towns. One day, though, ol' Rootilla Redgums and her grandson, Julius Jefferson, arrive. Rootilla teaches the citizens of Walkerton how to make all sorts of beautiful things, and the white people can't get enough. But some aren't so happy. When a hooded mob threatens to burn down the town, Julius and Rootilla must work wonders to protect Walkerton and its people—even if it means moving heaven and earth itself. With exquisite cinematic illustrations by John Holyfield and a generous trim size, this portrait of Black endurance draws on the rhythms and traditions of African American storytelling to open a powerful window into the past.